Modelling interception loss from evergreen oak Mediterranean savannas: Application of a tree-based modelling approach - Pereira, F. L.; Gash, J. H. C.; David, J. S.; David, T. S.; Monteiro, P. R.; Valente, F. (Agricultural and Forest Meteorology, 2009)
In a previous study, it was shown that an isolated, fully saturated tree-crown behaves like a wet bulb, allowing evaporation of intercepted rainfall to be estimated by a simple diffusion equation for water vapour. This observation was taken as the basis for a new approach in modelling interception loss from savanna-type woodland, whereby the ecosystem evaporation is derived by scaling up the evaporation from individual trees, rather than by considering a homogeneous forest cover. Interception loss from isolated trees was estimated by combining the aforementioned equation for water vapour ﬂux with Gash’s analytical model. A new methodology, which avoids the subjectivity inherent in the Leyton method, was used for estimating the crown storage capacity. Modelling performance was evaluated against data from two Mediterranean savanna-type oak woodlands (montados) in southern Portugal. Interception loss estimates were in good agreement with observations in both sites. The proposed modelling approach is physically based, requires only a limited amount of data and should be suitable for the modelling of interception loss in isolated trees and savannatype ecosystems
Keywords: Gash analytical model; Isolated trees; Quercus ilex; rainfall interception; Savannas; Wet bulb temperature

Water-use strategies in two co-occurring Mediterranean evergreen oaks: surviving the summer drought - David, T. S.; Henriques, M. O.; Kurz-Besson, C.; Nunes, J.; Valente, F.; Vaz, M.; Pereira, J. S.; Siegwolf, R.; Chaves, M. M.; Gazarini, L. C.; David, J. S. (Tree Physiology, 2007)
In the Mediterranean evergreen oak woodlands of southern Portugal, the main tree species are Quercus ilex ssp. rotundifolia Lam. (holm oak) and Quercus suber L. (cork oak). We studied a savannah-type woodland where these species coexist, with the aim of better understanding the mechanisms of tree adaptation to seasonal drought. In both species, seasonal variations in transpiration and predawn leaf water potential showed a maximum in spring followed by a decline through the rainless summer and a recovery with autumn rainfall. Although the observed decrease in predawn leaf water potential in summer indicates soil water depletion, trees maintained transpiration rates above 0.7 mm day−1 during the summer drought. By that time, more than 70% of the transpired water was being taken from groundwater sources. The daily fluctuations in soil water content suggest that some root uptake of groundwater was mediated through the upper soil layers by hydraulic lift. During the dry season, Q. ilex maintained higher predawn leaf water potentials, canopy conductances and transpiration rates than Q. suber. The higher water status of Q. ilex was likely associated with their deeper root systems compared with Q. suber. Whole-tree hydraulic conductance and minimum midday leaf water potential were lower in Q. ilex, indicating that Q. ilex was more tolerant to drought than Q. suber. Overall, Q. ilex seemed to have more effective drought avoidance and drought tolerance mechanisms than Q. suber.
10.1093/treephys/27.6.79310.1093/treephys/27.6.793
Keywords: canopy conductance; groundwater; Hydraulic conductance; leaf water potential; Quercus ilex; Quercus suber; sap flow

Rainfall interception by an isolated evergreen oak tree in a Mediterranean savannah - David, T. S.; Gash, J. H. C.; Valente, F.; Pereira, J. S.; Ferreira, M. I.; David, J. S. (Hydrological Processes, 2006)
Redistribution of ground-level rainfall and interception loss by an isolated Quercus ilex tree were measured over 2 years in a Mediterranean oak savannah. Stemﬂow, meteorological variables and sap ﬂow were also monitored. Rainfall at ground level was measured by a set of rain-gauges located in a radial layout centred on the tree trunk and extending beyond the crown limits. Interception loss was computed as the difference between the volume of rainwater that would reach the ground in the absence of the tree and the volume of water that actually fell on the ground sampling area (stemﬂow included). This procedure provided correct interception loss estimates, irrespective of rainfall inclination. Results have shown a clear non-random spatial distribution of ground-level rainfall, with rainwater concentrations upwind beneath the crown and rain-shadows downwind. Interception loss amounted to 22% of gross rainfall, per unit of crown-projected area. Stand interception loss, per unit of ground area, was only 8% of gross rainfall and 28% of tree evapotranspiration. These values reﬂect the low crown cover fraction of the stand (0Ð39) and the speciﬁc features of the Mediterranean rainfall regime (predominantly with few large storms). Nevertheless, it still is an important component of the water balance of these Mediterranean ecosystems
Keywords: interception loss; Isolated trees; Quercus ilex; rainfall interception; rainfall redistribution

Seasonal Variations in Soil and Plant Water Status in a Quercus suber L. Stand: Roots as Determinants of Tree Productivity and Survival in the Mediterranean-type Ecosystem - Otieno, D. O.; Kurz-Besson, C.; Liu, J.; Schmidt, M. W. T.; Do, R. Vale-Lobo; David, T. S.; Siegwolf, R.; Pereira, J. S.; Tenhunen, J. D. (Plant and Soil, 2006)
Studies were conducted to examine changes in soil (Ys) and plant water status during summer in a 16-year old Quercus suber plantation in southern Portugal. Continuous measurements were conducted between May 2003 and August 2004, while discontinuous measurements were conducted on a monthly basis between May and September 2003 and repeated between March and September 2004. Intensive measurements were conducted on ﬁve trees with mean height and DBH of 5.3 m and 11.6 cm, respectively, growing at close proximity to each other. Weather conditions and soil water potential (Ys) at the rhizosphere of each of the trees measured at 0.3 and 1 m soil depth were continuously monitored. Predawn (Ypd) and midday (Ymd) leaf water potentials were determined every month. Soil and plant samples were also collected in June and September from diﬀerent locations within the study site for d 18 O isotope composition analysis. Pressure–volume (p–v) curves were constructed from plant shoots at diﬀerent times during the vegetative period to determine osmotic potential at full saturation (P 100 ), water potential at turgor loss point (Ytlp), relative water content at turgor loss point (R*tlp) and bulk modulus of elasticity (e). Signiﬁcant P < 0.05 decline in Ys occurred between May and September, the lowest value recorded being –2.0 MPa. Decline in soil moisture aﬀected tree water status, but decline in leaf water potential varied signiﬁcantly (P < 0.05) among the trees. At the end of summer drought, lowest Ypd measured was –1.7 MPa while the highest measured during this time was –0.8 MPa. Diﬀerences among trees were attributed to diﬀerences in rooting depth, as shown by regression analysis of 18 O isotopes. Radial stem growth ceased when Ys within the upper 0.3 m depth approached –1.5 MPa. The upper soil layers contributed approximately 33% of the total tree water requirement, between spring and mid summer when drought was experienced by trees. Deep soil layers however, supplied most of the water required during drought and no growth was recorded during this time. Stressed trees increased solute concentration of their tissues by a Magnitude of 0.7 MPa while bulk tissue elastic modulus increased by about 17 MPa. The study emphasizes the signiﬁcance of roots as determinants of tree productivity and survival in the Mediterranean ecosystems.
Keywords: Drought stress; leaf water potential; osmotic adjustment; oxygen isotope; root distribution